Archaeological approaches to shamanism : mind-body, nature, and culture - Gheorghiu, Dragos; Pásztor, Emília; Bender, Herman; Nash, George (Cambridge Scholars Publishing, 2017)
"This long awaited book discusses both ancient and modern shamanism, demonstrating its longevity and spatial distribution. The book is divided into eleven thought-provoking chapters that are organised into three sections: mind-body, nature, and culture. It discusses the clear associations with this sometimes little-understood ritualised practice, and asks what shamanism is and if tangible evidence can be extracted from a largely fragmentary archaeological record. The book offers a novel portrayal of the material culture of shamanism by collating carefully selected studies by specialists from three different continents, promoting a series of new perspectives on this idiosyncratic and sometimes intangible phenomenon."--Back cover